Analisis Penyerapan Anggaran Pada Satuan Kerja Perangkat Aceh - Nurul Fajar; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2017)
The absorption of SKPD (govemental working unit/institution) budget contribute to the local government budget absorption as measured by the proportion of the budget that has been disbursed by working unit in one fiscal year. Absorption can be interpreted to compare the budget cap that has been established with a budget that has been realized. This study aimed to analyze the budget absorption in work units Aceh (SKPA). The population in this study was all SKPA (45 SKPA). The results showed that with the implementation of the comparison realization of the budget with a target budget absorption, consistency in the implementation of programs / activities, schedule accuracy withdrawal of your budget can increase budget spending on each SKPA.KEYWORDS : Absorption of the budget, Budget of Goverment, APBD